تحليل عوامل صعوبات قراءة النصوص اللغة العربية في الصف الخامس بمدرسة المرشيد الإبتدائية الإسلامية باندونج - Cahyani, Esa; Siti Sanah (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
Reading skills are one of the language skills in learning Arabic after speaking skills. Maharah qiraah is the ability to read Arabic texts fluently, in accordance with the correct pronunciation of letters, vowels, and Arabic grammar, and to understand the content of the texts accurately. However, many problems are encountered by students when learning Arabic as a foreign language in Indonesia. This study aims to identify the factors that cause difficulties in reading Arabic texts among fifth grade students at Madrasah Ibtidaiyah Al Mursyid. This research employs a descriptive qualitative approach with a population of 17 students, and the sample used in this study is a total sample. Data were collected through observation, interviews, questionnaires, and documentation. The research was conducted at Madrasah Ibtidaiyah Al Mursyid in Cicaheum, with data sources including fifth grade students and Arabic language teachers. The results of the study indicate that the factors causing difficulties for fifth grade students in reading Arabic can be classified into four categories: linguistic factors, non linguistic factors, internal factors, and external factors.